PATERNITY DALAM PERSPEKTIF HUKUM ISLAM PADA NEGARA-NEGARA MUSLIM DI DUNIA - Adji Pratama Putra (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
This study examines the legitimacy of children, child custody, and child guardianship from the perspective of Islamic law in Muslim countries in the world. This study aims to determine how the implementation of child legitimacy, child custody, and child guardianship from the perspective of Islamic law in Muslim countries in the world. This research uses library research by collecting qualitative data. Data was obtained by collecting from several sources such as books and journal articles. The approach in this research is normative by analyzing the existing rules in several countries relating to the legitimacy of children, child custody, and child guardianship that already exist and are clearly described. The results of this study indicate that child legitimacy, child custody, and child guardianship have different provisions and are regulated in different laws in every Muslim country in the world.Abstrak.